HUBUNGAN ANTARA BUDAYA ORGANISASI DENGAN KEPUASAN KERJA GURU SUNSHINE KIDS EDUCATION DI PONTIANAK - B31109040, RYAN LIONER (Jurnal Manajemen Update, 2013)
The purpose of this study was to determine the relationship between organizational culture with job satisfaction of teachers at Sunshine Kids Education in Pontianak. This study is a correlational research. Organizational culture consists of 7 variables, that is innovation and risktaking culture (X1), attention to detail culture (X2), processorientation culture (X3), people orientationculture (X4), teamorientation culture (X5),aggressiveness culture(X6 ), and stability culture (X7), while job satisfaction as a Y variable.The sample used in this study were 21 respondents who are all teachers at Sunshine Kids Education. The data collected by using questionnaires with sampling technique using saturated sampling technique. This study used a non-parametric statistical using Kendall Tauanalysis tools. Data were processed by using SPSS 19. The analysis showsfrom 7variabels,onlyteam orientation cultureandstability culturehasa significantrelationshipwith job satisfactionof teachersin the SunshineKidsEducation, whilevariabelsinnovation andrisk taking culture,attentionto detail culture, proccess orientation culture, peopleorientation culture, andaggressivenessculture did nothave a significant relationshipwithjob satisfactionof teachersin theSunshineKidsEducation. Keywords: Organizational Culture, Job Satisfaction.